STUDY OF CONSUMPTION BEHAVIOR AND ITS MAIN FACTORS OF INFLUENCE IN THE CURRENT ECONOMIC AND SOCIAL CONTEXT - CRISTINA GHERMAN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2020)
Knowing the consumption behavior of individuals is a basic goal of any business, the market success depending decisively on the ability of organizations to adapt to the ever-changing needs and preferences of consumers. The phenomenon of business globalization, but also the technological innovations of the last decades have created new possibilities for selling goods/services and have implicitly ensured the access of a growing number of consumers to the products they need, regardless of the country/continent of origin. In the current economic and social context generated by the onset of the coronavirus pandemic, there are significant changes in the consumption behavior, both in terms of its content and its manifestation. Given these aspects, this paper analyzes the results of a qualitative marketing research, in close correlation with statistical data on household expenditure by consumption purpose, at national and European level. The research was based on the method of the semi-structured in-depth interview and focused on highlighting the main characteristics of consumption behavior, as well as the changes determined by the current context of the coronavirus pandemic. The results of marketing research showed new trends in the consumption behavior of individuals, requiring a reassessment of companies' strategies to adapt their activity to the new market conditions.